2019
DOI: 10.1017/s1751731118001684
|View full text |Cite
|
Sign up to set email alerts
|

Follicular development of sows at weaning in relation to estimated breeding value for within-litter variation in piglet birth weight

Abstract: In this study we aimed to identify possible causes of within-litter variation in piglet birth weight (birth weight variation) by studying follicular development of sows at weaning in relation to their estimated breeding value (EBV) for birth weight variation. In total, 29 multiparous sows (parity 3 to 5) were selected on their EBV for birth weight variation (SD in grams; High-EBV: 15.8±1.6, N=14 and Low-EBV: -24.7±1.5, N=15). The two groups of sows had similar litter sizes (15.7 v. 16.9). Within 24 h after par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The metabolic rate during lactation differs between sows with equitable feeding [39] and sows with higher weight loss during lactation have longer weaning-to-estrus intervals [40]. The ovarian response to gonadotropins post-partum and during lactation are regulated by insulin and the insulin-like factor (IGF-I), and sows metabolically compromised after farrowing have reduced both insulin and IGF-1 levels [41], which has a negative impact on the ovarian follicular development [19,42,43]. Lucy [41] indicated that this mismatch could persist during lactation and weaning.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic rate during lactation differs between sows with equitable feeding [39] and sows with higher weight loss during lactation have longer weaning-to-estrus intervals [40]. The ovarian response to gonadotropins post-partum and during lactation are regulated by insulin and the insulin-like factor (IGF-I), and sows metabolically compromised after farrowing have reduced both insulin and IGF-1 levels [41], which has a negative impact on the ovarian follicular development [19,42,43]. Lucy [41] indicated that this mismatch could persist during lactation and weaning.…”
Section: Discussionmentioning
confidence: 99%
“…The sow is supposed to eat enough to meet the nutrient requirements of growing litters prior to farrowing, which may cause some of the problems seen around the time of farrowing [9,10]. During the early stage of lactation, sows with large litters loose more energy while producing more milk that cannot match up with the energy from their feed, ending up in a negative energy balance (NEB) [11,12]. Negative energy balance impacts follicle development after weaning [13][14][15], oocyte quality [13,14], embryo development [11,16], and piglet birth weight [17].…”
Section: A C C E T E Dmentioning
confidence: 99%
“…Therefore, follicular growth after weaning in these sows might be compromised. Recently, Costermans et al [8] demonstrated that a higher weight loss during lactation was also related to a lower percentage of healthy cumulus-oocyte complex. These findings indicate that season or climatic factors may influence feed intake and body weight loss of sows during lactation, and thus, has a significant impact on the response of sows to GnRH treatment.…”
Section: Discussionmentioning
confidence: 99%